SISTEM INFORMASI PEMESANAN DAN PENGELOLAAN BAHAN BAKU BERBASIS WEB - Rahimullaily; Sri Restu Ningsih; Ratih Purwasih; Rara Meisa Putri (Jurnal Informatika Kaputama (JIK), 2025)
Sosro’s Cafe, a food and beverage business at GOR Haji Agus Salim, faces challenges in managing raw material orders due to still using manual recording, which is prone to errors and lacks accuracy. Consequently, overstocking or understocking frequently occurs, along with disorganized record-keeping. Managing raw material reports is also difficult because stock data is hard to find and access. To overcome these problems, a web-based information system is needed to assist the owner and employees in ordering and recording incoming and outgoing raw materials, and generating raw material reports. The software development method chosen to build this system is the waterfall model, utilizing PHP and MySQL. The final result is the creation of a system that improves the efficiency of ordering and managing raw materials, thus making the performance of the owner and employees of Sosro’s Cafe more effective